Kein Platz für Flüchtlinge? Eine empirische Untersuchung der Ausgrenzung Geflüchteter am Beispiel der Stadt Bautzen - Kurtenbach, Sebastian (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
The paper discusses how it becomes common behaviour to exclude refugees in a middle-town. Therefore, an analytical model of hostile social spaces is formulated, which explains the exclusion of branded foreign groups. Precondition is a change in what is considered as a normal social behaviour. Through this, the newly developed collective norms of a local society justify the exclusion of specific groups such as refugees. Using Bautzen (Germany) as an example, the local discussion about refugees as well as their perception is debated. Therefore, the discourse about refugees and violence against them is analysed in newspaper articles as well as in minutes of political debates. In the center of the analysis are 106 semi-structured interviews with various social groups. So, the change of normality as well as the contextual effect, operationalized as the exclusion of refugees, are analysed. The results show a change of what is looked at as normal as well as that the exclusion of refugees is justified and not sanctioned in wide parts of the local society. Refugees report of exclusion and violence in different arenas like educational institutions, public spaces or the public transport network. The paper ends concluding additional need for research defining which sociostructural dynamics are preconditions for the developing of hostile places.